Selective shaping of prokaryotic communities and core symbiont maintenance suggest large-scale aquarium facilities as reservoirs of microbiome diversity in octocorals - Marques, Matilde; Pascoal, Francisco; Villela, Helena; Santos, Elsa; Baylina, Núria; Peixoto, Raquel S.; Keller-Costa, Tina; Costa, Rodrigo (Frontiers in Microbiology, 2025)
IntroductionOctocorals play a critical role in coral ecosystems, contributing to habitat complexity and marine biodiversity. Despite their ecological importance, the microbial communities associated with octocorals remain understudied, particularly under ex situ conditions.MethodsThis study compared the prokaryotic communities of the tropical octocoral Litophyton sp., surrounding seawater, and sediments (“biotopes”) from a natural Red Sea reef and a long-term tropical aquarium mesocosm designed to emulate natural reef ecosystems (“habitats”). Using high throughput 16S rRNA gene sequencing, we assessed community composition, diversity, and core taxa.ResultsDistinct prokaryotic assemblages were associated with each biotope, with core symbionts persisting across habitats. While seawater communities diverged between habitats, sediment communities were compositionally more similar, dominated by Nitrosopumilaceae, Pirellulaceae, Woeseiaceae, and Flavobacteriaceae. Litophyton sp. harbored specific symbionts consistently across habitats. Alpha-diversity in Litophyton sp. did not differ significantly between habitats (ANOVA with Tukey’s HSD, p > 0.05), and beta-diversity patterns were also not significant (PERMANOVA, p > 0.05). We identified 19 ASVs shared across Litophyton sp. habitats, dominated by Endozoicomonas, unclassified Campylobacterales, and Marivibrio. Several core families, such as Endozoicomonadaceae, Spirochaetaceae, and Kiloniellaceae were consistently associated with Litophyton sp. across habitats, indicating stability of specific host-microbe associations even after 25 years in aquarium conditions. Phylogenetic analysis further demonstrated the selective maintenance of diverse Endozoicomonas lineages in aquarium-kept Litophyton specimens.DiscussionThese findings suggest that large-scale aquarium ecosystems can preserve, to some extent, the structure and diversity of coral-associated microbiomes over extended time periods. By supporting key symbiotic taxa, multi-trophic integrated aquarium systems may serve as repositories for healthy coral-associated microbial communities and microbiome stewardship, underscoring their value in future conservation efforts to sustain the biodiversity of marine holobionts in the face of growing environmental challenges.